Depression of contact sensitivity by Pseudomonas aeruginosa-induced suppressor cells which affect the induction phase of immune response. - Garzelli, C (1979)
The cellular basis of depression of contact sensitivity to oxazolone in mice injected with Pseudomonas aeruginosa was studied. Cells from draining lymph nodes of mice sensitized with oxazolone 18 h previously were able to induce contact sensitivity to normal mice when administered in their footpads. In contrast, cells from draining lymph nodes of P. aeruginosa-injected and oxazolone-sensitized donors failed to induce contact sensitivity when injected in the footpad of normal mice and were capable of actively blocking the immunizing process brought about by lymph node cells from sensitized mice when injected together in the footpad of normal recipients. The P. aeruginosa-induced suppressor cells required antigenic stimulation, had precursors sensitive to cyclophosphamide, and did not affect the effector mechanisms of contact sensitivity. Thus, the results suggest that P. aeurginosa depresses contact sensitivity to oxazolone by enhancing the activity of suppressor cells which normally arise during the sensitization process and which affect the afferent limb of the immune response, probably by inhibiting the normal recruitment of T lymphocytes in the draining lymph nodes.